STRUKTUR NARASI NOVEL CA BAU KAN, KARYA REMY SYLADO ANALISIS SEMIOTIK - Sri Sabakti (Madah: Jurnal Bahasa dan Sastra, 2013)
This research is aimed to expose the narrative structure of the novel Ca Bau Kan by using semiotical theory. The source of the data is the novel Ca Bau kan written by Remy Silado and published by KPG, eight edition, 2004. The data is collected by doing the library research. The teory applied in this research is the semiotical theory, especially the literary analysis of Subur Laksono Wardoyo that the analysis of the text of prose can be applied by using three fases; the analysis of the basic scheme narrative, the analysis of mean signifier, and the analysis of syntagmatics and pragmatics. The result of this research showed that the narrative structure in the novel CBK that (1) the life of Tinung before being a ca bau kan, (2) the life of Tinung as a ca bau kan, and (3) the life of Tinung after not being a ca bau kan anymore. Based on the narrative structure, it was found that “ Love is only one. No measurement is needed” is the mean signifier and able to be clarified by  the analysis of syntagmatics-paradigmatics based on the biner oposition of weak x strong.